External Evaluation of Schools: results and self- evaluation. What relationship? (Foro de Educacion, 2012)
In Portugal, in the years 2006-2011, the General Inspection of Education has developed a program to evaluate schools. In this period were evaluated in 1107 schools. For each school, the evaluation team prepared a report. Each school was evaluated based on a model that took into account five domains (Results, Provision of educational services, school organization and management, leadership and capacity for self-regulation and school improvement). Based on the scores given to each school in the areas of results and self-evaluation, we verify that the 287 schools evaluated in 2008-2009, the scores of these areas showed correlation.Thus, the results of our study, corroborating other studies, suggest that the self-evaluation influences educational outcomes.